Dosing study of massage for chronic neck pain: protocol for the dose response evaluation and analysis of massage [DREAM] trial - Sherman Karen J; Cook Andrea J; Kahn Janet R; Hawkes Rene J; Wellman Robert D; Cherkin Daniel C (BMC, 2012)
Abstract Background Despite the growing popularity of massage, its effectiveness for treating neck pain remains unclear, largely because of the poor quality of research. A major deficiency of previous studies has been their use of low "doses" of massage that massage therapists consider inadequate. Unfortunately, the number of minutes per massage session, sessions per week, or weeks of treatment necessary for massage to have beneficial or optimal effects are not known. This study is designed to address these gaps in our knowledge by determining, for persons with chronic neck pain: 1) the optimal combination of number of treatments per week and length of individual treatment session, and 2) the optimal number of weeks of treatment. Methods/design In this study, 228 persons with chronic non-specific neck pain will be recruited from primary health care clinics in a large health care system in the Seattle area. Participants will be randomized to a wait list control group or 4 weeks of treatment with one of 5 different dosing combinations (2 or 3 30-min treatments per week or 1, 2, or 3 60-min treatments per week). At the end of this 4-week primary treatment period, participants initially receiving each of the 5 dosing combinations will be randomized to a secondary treatment period of either no additional treatment or 6 weekly 60-min massages. The primary outcomes, neck-related dysfunction and pain, will be assessed by blinded telephone interviewers 5, 12, and 26 weeks post-randomization. To better characterize the trajectory of treatment effects, these interview data will be supplemented with outcomes data collected by internet questionnaire at 10, 16, 20 and 39 weeks. Comparisons of outcomes for the 6 groups during the primary treatment period will identify the optimal weekly dose, while comparisons of outcomes during the secondary treatment period will determine if 10 weeks of treatment is superior to 4 weeks. Discussion A broad dosing schedule was included in this trial. If adherence to any of these doses is poor, those doses will be discontinued. Trial registration This trial is registered in ClinicalTrials.gov, with the ID number of NCT01122836